Adipokine zinc-alpha-2-glycoprotein as a novel urinary biomarker presents earlier than microalbuminuria in diabetic nephropathy. (April 2016) - Wang, Yuan; Li, Yan-Mei; Zhang, Shu; Zhao, Jiu-Yang; Liu, Chun-Yan
Objective: To investigate the role of zinc-alpha-2-glycoprotein (ZAG) in the early stage of diabetic nephropathy, in patients with type 2 diabetes mellitus (T2DM). Methods: This cross-sectional observational study recruited patients with longstanding T2DM and healthy control subjects. Patients with T2DM were further stratified based on their urine albumin–creatinine ratio (UACR) and estimated glomerular filtration rate (eGFR). Serum and urine concentrations of ZAG were determined using an enzyme-linked immunosorbent assay. Results: Eighty patients with T2DM and 20 healthy control subjects were enrolled in the study. Mean ± SD concentrations of ZAG in serum and urine were both significantly higher in patients with T2DM (serum: 38.29 ± 22.72 mg/l; urine: 53.64 ± 29.48 mg/g) compared with concentrations in healthy control subjects (serum: 21.61 ± 8.83 mg/l; urine: 28.17 ± 10.64 mg/g). Serum ZAG concentration was positively correlated with serum creatinine and eGFR. Urine ZAG concentration was positively correlated with UACR. Urine concentration of ZAG in the higher eGFR group was higher than that in the normal eGFR group (41.26 ± 13.67 versus 32.05 ± 8.55 mg/g, respectively). Conclusion: These preliminary findings suggest that ZAG might be a potentially useful biomarker for early diagnosis of diabetic nephropathy in patients with T2DM.